Bimbingan Rohani Islam dalam Mengembangkan Spiritual bagi Korban Penyalahgunaan Napza - Leli Istikomah; Karomatun Nisak; Nur Azizah (Da'wah Faculty of UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
The problem of drug abuse requires professional and serious handling because drug users can come from all walks of life and all ages. Treatment for victims of drug abuse (residents) can be through social rehabilitation with various programs and services to help residents recover; one of the programs is Islamic spiritual guidance services. This study aims to explain the implementation of spiritual guidance for spiritual development, which is carried out at the